THE ROLE OF THE UNIVERSITY ENVIRONMENT IN ENCOURAGING STUDENTS TO ADOPT ENTREPRENEURIAL BEHAVIOR: A FIELD STUDY ON MASTER 2 STUDENTS AT BORDJ BOU ARRERIDJ UNIVERSITY - Djaghballou Hamza; Houria Nasri (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to highlight the role of the university environment in motivating students to adopt entrepreneurial behavior, considering that today’s university is a modern institution that seeks to link academic training with the labor market through the inclusion of ىentrepreneurship modules, the organization of scientific events, and the activation of spaces that support entrepreneurial orientation. To achieve this, a field study was conducted among Master 2 students in the Faculty of Social and Human Sciences, specializing in Sociology of Organization and Work, Sociology of Education, and Sociology of Communication. The descriptive-analytical method was adopted, relying on the questionnaire technique to collect field data from a purposive sample of 46 sociology students. The data were processed and analyzed using the SPSS program. The study concluded that the content of the entrepreneurship course aligns with labor market requirements and contributes to equipping students with skills that encourage them to build entrepreneurial projects. Moreover, scientific events help enhance creative abilities, especially among female students. In addition, business incubators play a crucial role in developing students’ capacities to provide specialized services—including funding, guidance, and support—which strengthens their adoption of entrepreneurial behavior.